Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Modal Terhadap Earnings Response Coefficient - Wahasusmiah, Rolia; Indriani, Poppy (Universitas Muhammadiyah Semarang, 2022)
This research is meant to examine the influence of Profitability, size, and Capital Structure on the earning response coefficient by taking the population of this research, manufacturing companies listed in Indonesia StockExchange in 2017-2019. The research samples have been selected using a purposive sampling technique, so 34 companies (102 firm years) which have met the criteria have been chosen as samples. The data analysis technique has been done using multiple regressions and hypothesis tests using the SPSS25st version. Based on the result of multiple regressions analysis with 5%significancelevel, therefore the result of this research shows that: (1) Profitability has an influence on the earning response coefficient with the value of the regression showing positive and unidirectional correlation so that the first hypothesis is accepted; (2) Firm size has an influence to the earning response coefficient and shows positive unidirectional correlation, so that second hypothesis is accepted; (3) Capital Structure has an influence to the earning response coefficient, and the regression value shows positive and unidirectional correlation so that the third hypothesis is accepted.